2022
DOI: 10.35378/gujs.930412
|View full text |Cite
|
Sign up to set email alerts
|

A New Methodology to Describe Non-Linear Characterization Depending on Temperature of a Semi-Active Absorber Based on Bouc-Wen Model

Abstract: Highlights• A new methodology to describe dynamic behaviours of MR absorber depending on temperature.• Bouc-Wen model for temperature changing.• The damper force defined depending on temperature with a single equation.• Control comfortably and more stability MR absorber on a structure, vehicle, and medical haptic.• The rheological test of MR fluid and MR absorber tests under different temperature conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…It has been also identified that the rate of increase in the MRF temperature in the working area of the damper with the insulation material could be reduced by 57.4% compared to that of the damper without the insulation material. Parlak et al [82] identified the relationship between the damping performance and temperature in the control algorithms using a new methodology, which considers the dynamic behaviors of the MR damper depending on the temperature based on the Bouc-Wen model. After evaluating seven parameters in the Bouc-Wen model related with the temperature, the damping force was defined depending on the temperature, with a single equation that significantly simplifies the control process.…”
Section: Thermal Effect In Application Systemsmentioning
confidence: 99%
“…It has been also identified that the rate of increase in the MRF temperature in the working area of the damper with the insulation material could be reduced by 57.4% compared to that of the damper without the insulation material. Parlak et al [82] identified the relationship between the damping performance and temperature in the control algorithms using a new methodology, which considers the dynamic behaviors of the MR damper depending on the temperature based on the Bouc-Wen model. After evaluating seven parameters in the Bouc-Wen model related with the temperature, the damping force was defined depending on the temperature, with a single equation that significantly simplifies the control process.…”
Section: Thermal Effect In Application Systemsmentioning
confidence: 99%